KOMUNIKASI ORGANISASI PIMPINAN DAERAH MUHAMMADIYAH KOTA BENGKULU - Mulkan Habibi (JOISCOM (Journal of Islamic Communication), 2020)
ORGANIZATIONAL COMMUNICATION OFMUHAMMADIYAH REGIONAL LEADERSHIP  OF BENGKULU CITYBy:Mulkan HabibiMuhammadiyah University of JakartaEmail: mulkanhabii17@gmail.com ABSTRACT Organizational communication is a form used in an organization, in the form of sending or delivering messages / information and receiving various organizational messages in formal and informal groups within an organization. The formulation of the problem in this study was How the organizational communication of the Muhammadiyah regional leadership of Bengkulu city during the 2015-2020 Period. The purpose of this study was to determine the organization communication of Muhammadiyah Regional Leadership of Bengkulu City. The method used in this study was qualitative with a qualitative descriptive approach, and the data collection techniques, namely: observation, interview, and documentation. Based on the results of the study showed that the organizational communication of Muhammadiyah regional leadership with Muhammadiyah branch leaders of Bengkulu City used the Downward Communication, and Upward Communication ways, but the ways that were carried out could not be implemented properly. It was because the problems of the people in the organization have their respective activities, so that when there was a meeting, it was often those who were unable to attend, but they have to accept the decision of the meeting held. Keywords: Communication, Organization, Muhammadiyah